Age-related cardiovascular response to tilt test in healthy volunteers of both sexes - Rimi, Sadia Afrin; Ferdousi, Sultana; Sultana, Shamima (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This study aimed to assess the age-related changes in the cardiovascular response to tilt test in 90 healthy individuals of both sexes (age range: 18-60 years). Tilting was done at 600 for 10 min using a motorized tilt table. The blood pressure was recorded by a sphygmomanometer. The heart rate and peripheral capillary oxygen saturation were measured by a pulse oximeter. In males, significantly lesser changes in the systolic, diastolic and mean arterial pressure were observed in the old age (47-60 years) than the young (18-32 years) and middle age (33-46 years) groups. Significantly lesser responses in the heart rate and systolic blood pressure change were observed in the old age females compared to young age after tilting. The rise of diastolic blood pressure after tilting was lesser in the old age female compared to both young and middle-age females. In conclusion, the aging process is associated with attenuated cardiovascular response to tilt test in both males and females.